The Effect of Using Small Group Discussions Through Zoom Breakout Room to Increase the Frequency of Individual Speaking Participation in the Speaking Courses - Lulu Zahrotun Nisa; Taqiya Nabila Prameswari; Yayah Izzah Alawiyah (Journal of Digital Learning and Education, 2021)
The purpose of this study is to determine whether the small group discussion method via breakout room zoom may boost student individual engagement in order for them to be more active and confident in learning speaking. This research study used a qualitative method with applied video analysis and questioners' perceptions of students as instruments. The findings found 17 active participants in the observation speaking class and 35 participants preferred small group discussions using the breakout room zoom application, with the majority preferring small group discussions because it helped them to be more active and confident. This method can also boost their confidence for more active participation for individual speaking in class, and they believe that small group discussions via breakout room zoom are the most effective way to deal with a pandemic.